Project-Based Curriculum Approach in Arabic Language Learning: Case Studies and Best Practices - Masitoh; Aziz, Muhammad Tareh (Journal of Practice Learning and Educational Development, 2025)
This article explores the application of a project-based curriculum approach (PBL) in Arabic language learning, with emphasis on case studies and best practices. This approach aims to enhance student engagement and material understanding by involving them in relevant and contextual projects. Through analysis of several cases from various educational institutions, this article identifies how PBL is applied and its impact on student learning outcomes. Projects such as video making of presentations, blogging, and simulation of real-life situations are integrated to enable students to apply Arabic language knowledge in a practical context. The best practices identified include clear project planning, the use of supportive technology, and structured evaluation. This article also discusses the challenges faced in the application of PBL, such as time management and training needs for teachers. By understanding and addressing these challenges, PBL can be an effective strategy for improving the quality of Arabic language learning.